Collaborative Intelligence and Digital Agency: Women’s Lived Experiences in Navigating Human-AI Interaction on Canva - Syammas Pinasthika Syarbini; Irmawan Rahyadi; Muhammad Aras; La Mani (FOUNDAE (Foundation of Advanced Education), 2026)
The rapid development of generative artificial intelligence (AI) has transformed digital creative practices, enabling users to produce visual content through AI-assisted design platforms. However, limited research has explored how everyday users experience collaboration with AI tools in creative production, particularly in relation to maintaining digital agency and creative control. This study aims to explore women’s lived experiences in interacting with Canva AI during visual content production and to understand how collaborative intelligence and digital agency emerge in AI-assisted creative practices. The study employed a qualitative approach using Interpretative Phenomenological Analysis (IPA). Data were collected through in-depth interviews with seven women who actively use Canva AI in their digital content production activities. The analysis identified four key experiential dimensions: reflexive agency, collaborative intelligence, ethical and cultural filtering, and digital empowerment. Participants treated AI-generated visuals as preliminary materials requiring human interpretation, refinement, and contextual judgment before publication. Canva AI was perceived as a co-creative partner that accelerated idea generation while preserving human control over the final design decisions. The findings suggest that collaborative intelligence in AI-assisted creativity functions as a partnership between human interpretation and technological support, where human agency remains central in shaping digital communication practices.